Space syntax theory and Durkheim's social morphology: a reassessment. Issue 2 (3rd May 2020) - Suonperä Liebst, Lasse; Griffiths, Sam
ABSTRACT: In outlining their influential architectural theory of space syntax, Hillier and Hanson acknowledge its affinity to Durkheim's sociological considerations on the spatial-morphological basis of social life. In doing so, space syntax theory promised to address the then woefully under-theorized relationship between society and space, specifically by emphasizing the agency of spatial-morphological arrangements. Given the Durkheimian inspiration, it is surprising that sociology has been so silent on the subject of space syntax. This lack of dialogue may be explained by the gestation of space syntax research within the specialist disciplinary silo of architectural theory, as well as by the default sociological assessment that formal methodologies of spatial analysis – such as those associated with space syntax – sustain a discredited fallacy of physical determinism. Yet, intellectually this situation is unfortunate: while sociology overlooks how space syntax theory has advanced the Durkheimian understanding of spatial morphologies, space syntax theory misses an opportunity to update and broaden its notion of social processes. In response, we revisit Durkheim's social morphology and review the strengths and deficits of Hillier and Hanson's consideration of Durkheimian theory. We identify how difficulties arise because of an over-reliance of space syntax theory on the structural-functionalist macro-wing of the Durkheimain tradition. To address this issue, we prepare the ground for a theoretical engagement between space syntax and the micro-sociological branch of Durkheiminan scholarship, and show how this tradition offers a more coherent means for translating the spatio-morphological insights of space syntax theory into contemporary debates in the sociology of space.